LncSSBP1 Functions as a Negative Regulator of IL-6 Through Interaction With hnRNPK in Bronchial Epithelial Cells Infected With Talaromyces marneffei - Li, Yinghua; Chen, Huan; Li, Shuyi; Li, Yu; Liu, Guangnan; Bai, Jing; Luo, Honglin; Lan, Xiuwan; He, Zhiyi (Frontiers in Immunology, 2020)
Talaromyces marneffei (TM) is an important opportunistic pathogenic fungus capable of causing disseminated lethal infection. In our previous study, we identified host lncRNAs and mRNAs that are dysregulated in TM-infected bronchial epithelial cells. In this report, we verified that IL-6, a key factor in acute inflammatory response, is downregulated in TM pathogenesis. To elucidate the mechanism of IL-6 regulation, we analyzed the coding/non-coding network, and identified lncSSBP1, a novel lncRNA that is upregulated by TM. Our results demonstrate that overexpression of lncSSBP1 decreases IL-6 mRNA expression, whereas knockdown of lncSSBP1 enhances IL-6 mRNA expression. Though lncSSBP1 is primarily localized to the nucleus, bioinformatics analysis suggests that it is unlikely to function as competing endogenous RNA or to interact with IL-6 transcription factors. Instead, RNA pull down and RNA immunoprecipitation assays showed that lncSSBP1 binds specifically to heterogenous nuclear ribonucleoprotein K (hnRNPK), which is involved in IL-6 mRNA processing. Our findings suggest that lncSSBP1 may affect IL-6 mRNA expression during TM infection through interaction with hnRNPk in bronchial epithelial cells. Our results suggest a novel pathway by which TM may suppress the immune response to its advantage.